Temporal variation of ocean color from modis data in south china sea - Nursyafika Mamat, 1991-; Samsudin Ahmad, supervisor; Fakulti Geoinformasi dan Harta Tanah (2014)
Project Paper (Sarjana Muda Sains (Remote Sensing)) - Universiti Teknologi Malaysia, 2014